Internet Accounting Dictionaries: Present Solutions and Future Opportunities - Nielsen, Sandro; Mourier, Lise (HERMES - Journal of Language and Communication in Business, 2005)
An examination of existing accounting dictionaries on the Internet reveals a general need for a new type of dictionary. In contrast to the dictionaries now accessible, the future accounting dictionaries should be designed as proper Internet dictionaries based on a functional approach so they can be used in communication-oriented and knowledge-oriented situations. The lexicographers need to take a large number of aspects into consideration and this should be done by identifying the need of an international target group and present the data in such a way that the lexicographical information costs are kept at a low level.